Infanticides in Dakar: Medico-Legal Aspects - Mohamed Maniboliot Soumah1, 2, Peace Renée Senami Akokbegan3, Mor Ndiaye1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Infanticide is a crime that evokes emotion and misunderstanding in the general population. The overall objective was to assess the current situation regarding the killing of new-born children in Dakar. This is a cross-sectional, descriptive study spread over a 12-year period from 1 January 2004 to 31 December 2015. The study population was women accused of infanticide incarcerated in the prison and correctional facility of Liberté 6 and who had either been tried or who were awaiting trial during the study period. The 46 cases tried concerned 47 newborns and one mother having killed both her babies. The victims were found especially in the mother’s home (28 cases) For all women in our sample, the murder was motivated by personal, social and economic factors. The average age of the mothers was 25.5 years with the youngest being 17 years old and the oldest 41 years old. These detention periods ranged from 2 to 6 years. The average length of pre-trial detention was 3.26 years, The preventive strategies put in place in some countries are proof that prevention against these acts remains possible.